Administrative activity as characteristic of public administration - Hrechaniuk, Roksolana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
In the article the conducted development of theoretical aspects of determination of administrative activity is as part of state administration. The different scientific looks researched for formulation of concept of administrative activity, the basic constituents of this concept are certain in relation to state administration. To understand the nature of the administrative activity, it is necessary to research different approaches to its understanding. Analysis of publications allows to consider administrative activity as: part of public administration; component of activities of law enforcement agencies; administrative management. The main purpose of administrative activity as a characteristic of public administration is assurance of internal administration of performance of defined public tasks and strategic priorities of respective subject. Its effectiveness (through successful operational model, management decisions, administrative methods) can improve the quality of the statehood strategy in a specific area, sometimes by hiding its disadvantages. Administrative activity in public administration has certain features, which are related primarily to the fact that spheres of state influence are too diverse and, correspondingly, administrative processes in public administrative subjects differ depending on the need to perform certain tasks.